Approaching detachment in I-mode—response of core confinement and the edge pedestal in the ASDEX Upgrade tokamak. (15th February 2021) - Happel, T.; Reinke, M.L.; Silvagni, D.; Bernert, M.; Grover, O.; Hennequin, P.; Hubbard, A.E.; Plank, U.; Trier, E.; Brida, D.; David, P.; Fischer, R.; et al.
Abstract: Experiments on nitrogen assisted divertor detachment in the improved energy confinement mode (I-mode) are reported from the ASDEX Upgrade tokamak. When nitrogen is introduced into the divertor and radiation losses cool the divertor plasma down, a loss of core confinement is observed, concomitant with an increase in low frequency edge fluctuation levels. The loss in confinement can be compensated and the I-mode can be maintained by additional heating power input. Detachment of the inner divertor leg has been observed for the first time in an I-mode discharge. The outer divertor leg remains attached in these experiments. Good energy confinement properties ( H 98 ( y, 2) = 0.9) during the detachment of the inner divertor leg are reported.